Does 7E Cycle Model Improve Learning Environment? Evidence from Popular Fiction Classes - Andriadi, Andriadi; Arono, Arono; Yunita, Wisma; Zasrianita, Fera; Nadrah, Nadrah (Journal of English Education and Teaching, 2025)
The cultivation of 21st-century competencies within a constructivist learning environment opens avenues for students to discover their distinct strengths. Unfortunately, educators frequently neglect effective teaching models, hindering the creation of an ideal learning environment in literary education. This study examined how the 7E Learning Cycle Model impacts student performance in Popular Fiction classes. Additionally, it sought to uncover challenges faced by instructors teaching the Popular Fiction course and explore how they employ the 7E model to establish a conducive learning environment, ensuring successful outcomes in Popular Fiction classes. This study adopted Classroom Action Research. Data gathered through popular fiction analysis test, interview, observation, peer assessment, and other relevant documents. The study was conducted in the English Language Education Study Program of UIN Fatmawati Sukarno Bengkulu. 39 third semester students actively involved in seven week-learning popular fictions by using 7E Cycle Model. The research demonstrated notable improvements in Cycle I and Cycle II, with post-test scores rising from an average pre-test score of 63.23 to 79.59. In Cycle II, 82.01% of students achieved "Good" and "Very Good" ratings, indicating substantial progress. Positive outcomes encompassed active engagement, collaboration, independent knowledge construction, skill development, profound understanding, heightened critical thinking, and real-life context application. These results fostered sustained interest and motivation in the continuous learning cycle. Pedagogically, the study recommends the ongoing integration of the 7E Learning Model into the Popular Fiction curriculum, refining collaborative learning, and integrating technology for enhanced teaching effectiveness while addressing any limitations.